Counterargumentation at the primary level: An intervention study investigating the argumentative writing of second language learners. (April 2020) - Liu, Fulan; Stapleton, Paul
Abstract: Theory of mind, the capacity to imagine the thoughts of others, is a remarkable human ability, and this gift is essential for students to acknowledge alternative views when writing argumentative essays. However, evidence shows that this gift often goes unapplied by students at all levels. Numerous studies have revealed that students frequently fail to include opposing arguments whether they are writing in their native tongue or their second language. The present study, informed by genre theory, investigates the capacity of young students writing in their second language to generate counterarguments and include them in argumentative essays. A group of 11-year-old students received a 12-lesson classroom intervention focusing on counterargumentation using materials specially developed for the study. As part of the intervention, scripts were generated by 135 students in their second language, English, and coded for argumentative elements. Findings revealed the majority of students were able to generate counterarguments and rebuttals; however, special facilitative measures, including contextualizing, framing the topics and prompts, and using a highly prescriptive approach, were taken in light of the young age of the learners. This result indicates that instruction in written counterargumentation can be introduced as early as the primary level among second language learners.